A Study of Teaching Speaking Techniques Used at Peace English Course Pare, Kediri - Fahmi Farizi; Sakhi Herwiana (Pioneer: Journal of Language and Literature, 2022)
This research aimed to find out what teaching speaking techniques are used and the reasons for using the techniques by the tutors at Peace English Course, Pare, Kediri to overcome learners’ difficulties in speaking. The method of this research was a descriptive qualitative method. The researchers obtained the data by observing the three classes of speaking programs, interviewing the tutors of the three classes, and data documents from the Peace English Course. The finding of this research showed that the techniques applied by the tutors were Storytelling, conversation, presenting, problem-solving, discussion, debate, and speech. Story-telling and conversation were applied for the beginner level class while presentation, problem-solving, discussion, debate, and speech were applied for the advanced level class. The reasons for using the techniques were because they were considered fun and were able to make the learners practice more. For the learners who have difficulties in learning to speak, the tutors encourage and motivate them to practice more because every difficulty in the speaking learning process is considered to be easily solved by having more practice.